Persuading to Reflect: Role of Reflection and Insight in Persuasive Systems Design for Physical Health. (2nd November 2017) - Halttu, Kirsi; Oinas-Kukkonen, Harri
Abstract : Mobile applications and self-tracking devices help us to maintain health and support our goals in changing our behaviors. Most of these tools aim to increase our self-knowledge by providing information upon which to reflect. However, merely spending time reflecting does not always lead to insightful outcomes. In this study surveying users of mobile health and fitness applications ( N = 147), we have used structural equation modeling to explore the need for and roles of reflection and insight in the persuasive systems design model. The findings suggest that both dialogue support and primary task support features influence the need for reflection, paving the way to personal insight. The perceived credibility of the system played different roles for women and men and seemed to originate from different sources. In addition, we found significant roles for the attitude and unobtrusiveness of the system. This article contributes to positioning the reflective capabilities of a system in the design framework of persuasive systems and makes preliminary suggestions regarding how to transform the need for reflection into insights. It also exemplifies how to evaluate behavior change technologies by assessing the psychological outcomes of the intervention.